1993
DOI: 10.4319/lo.1993.38.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Aerobactin production by a planktonic marine Vibrio sp

Abstract: Production of siderophores by marine bacteria could potentially contribute to metal complexation by organic compounds in seawater. Direct isolation of planktonic marine bacteria on siderophore indicator plates showed that siderophore producers are present. The siderophore‐producing organisms that could be detected on this medium were more numerous in the mixed layer than in deeper water at this sampling site. One strain (DS40M5) was characterized and found to be a marine Vibrio sp. A siderophore produced by Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
113
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 7 publications
1
113
0
2
Order By: Relevance
“…Siderophore production is regulated by iron levels, with repression of siderophore biosynthesis under high iron conditions. Although the structures of many siderophores from terrestrial sources are known, only a few siderophore structures from marine bacteria have been fully characterized (Haygood et al 1993;Reid et al 1993;Butler 1998;Martinez et al 2000). Additional marine organisms (cyanobacteria and heterotrophic bacteria) have been shown to produce siderophores (Wilhelm and Trick 1994;Granger and Price 1999); however, the spectrum of siderophore types and functionalities produced in the ocean is only just beginning to be elucidated.…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 99%
See 3 more Smart Citations
“…Siderophore production is regulated by iron levels, with repression of siderophore biosynthesis under high iron conditions. Although the structures of many siderophores from terrestrial sources are known, only a few siderophore structures from marine bacteria have been fully characterized (Haygood et al 1993;Reid et al 1993;Butler 1998;Martinez et al 2000). Additional marine organisms (cyanobacteria and heterotrophic bacteria) have been shown to produce siderophores (Wilhelm and Trick 1994;Granger and Price 1999); however, the spectrum of siderophore types and functionalities produced in the ocean is only just beginning to be elucidated.…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 99%
“…After 2 d growth, the production of siderophore was assayed using chromazurol S (CAS) shuttle solution containing CAS/Fe(III)/HDTMA (hexadecyl-trimethylammonium) as described in Haygood et al (1993). The assay was positive using equal volumes of broth culture and CAS shuttle solution.…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery that siderophore-like compounds are produced by various marine microbes in laboratory culture, [66][67][68][69][70] and the similar conditional formation constants of seawater Fe-binding ligands and known siderophores suggested that the seawater ligands do have a direct biological origin and are probably not very large in molecular size (300-1000 Da). [71,72] This provokes the intriguing paradigm of microbes competing for this scarce trace element by sequestering a specific iron-collection 'agent'. Yet it raises important questions as well.…”
Section: The Provenance Of Ligandsmentioning
confidence: 99%